Evaluation of Improved Water Management Technology For Sustainable Crop Production System Under Both Canal And Tubewell Irrigation Command In West Bengal - Pramanick, Mahadev; Mallick, S.; Biswas, R.K. (Journal of Soil and Water Conservation, 2022)
A gap between created potential and utilization of irrigation water under both canal as well deep tubewell command has been existed in West Bengal. An attempt was made to identify the constraints through agro-ecological situation analysis, there after prioritized the problems and accordingly possible remedial measures were recommended. The situation specific problems were corrected through "On Farm Research" trials and then results were adopted through farmers participatozy approach. After 2-3 years of adoption of improved water management technology revealed that in canal command area under free flooding distribution system, 36% of potato growers, 25% of rapeseed and mustard growers and 50% of summer rice growers followed the proven technology, whereas in deep tubewell command, rational planning through spoutwise distribution of water with suitable crop choice found to narrow the gap.